High‐Efficiency Carbon‐Based CsPbIBr2 Solar Cells with Interfacial Energy Loss Suppressed by a Thin Bulk‐Heterojunction Layer. Issue 9 (4th August 2021) - Wang, Deng; Li, Wenjing; Li, Ruoshui; Sun, Weihai; Wu, Jihuai; Lan, Zhang
Abstract : The CsPbIBr2 perovskite has obvious advantages in balancing the stability and efficiency in inorganic perovskite solar cells (PSCs). Its large bandgap of 2.08 eV, which leads to a narrow spectral absorption (<600 nm), is the key limit to yielding a high power conversion efficiency (PCE). Herein, it is demonstrated that by integrating a thin bulk‐heterojunction (BHJ) layer (19 nm) composed of the typical poly (3‐hexylthiophene‐2, 5‐diyl) and [6, 6]‐phenyl methyl C61 butyric acid methyl ester (P3HT:PCBM) with CsPbIBr2 perovskite, a carbon‐based all‐inorganic PSC achieves a much higher champion PCE (11.54%) than the original CsPbIBr2 device (8.87%), and the value is also at the highest PCE level of all‐inorganic CsPbIBr2 PSCs. The integration of a thin BHJ layer brings an expanded light absorption range, better charge transfer dynamics, suppressed interfacial energy loss, and improved long‐term stability. The unencapsulated CsPbIBr2 PSC with an integrated BHJ layer shows excellent long‐term stability in an ambient atmosphere with high relative humidity (RH ≈ 45%, T ≈ 25 °C). Therefore, the BHJ integration is an effective strategy on the road to industrialization of carbon‐based all‐inorganic PSCs with low cost, high efficiency, and excellent long‐term stability. Abstract : Integrating a thin bulk‐heterojunction layer composed of the typical poly (3‐hexylthiophene‐2, 5‐diyl) and [6, 6]‐phenyl methyl C61 butyric acid methyl ester (P3HT:PCBM) in a carbon‐based all inorganic CsPbIBr2 perovskite solar cell can effectively suppress interfacial energy loss and greatly improve the power conversion efficiency from 8, 87% to 11.54%, which is also at the highest efficiency level of the reported counterparts.